On the question of the development of rural areas in Ukraine - Kupriianchyk, I. (Land Management, Cadastre and Land Monitoring, 2023)
The article explores the development of rural areas in Ukraine. In particular, the existing general problems of rural development were identified, the ways and prospects of their solution were outlined. It is determined that the key components of rural development are production (agricultural activities and other activities not related to agriculture), social (welfare, improving the quality of human capital in rural areas, preservation of traditions, moral and spiritual values), environmental conservation of natural resources of rural areas, environmentally friendly land use). It is substantiated that the interaction of these components will allow to form a social and economic environment for sustainable development of rural areas. The article states that the successful development of rural areas is to use an integrated approach to solving problems and conscientious fulfillment of obligations, which will increase the efficiency of community budgets and stabilize the social and economic situation of communities, regions and the country as a whole.